2021
DOI: 10.1186/s40658-021-00411-5
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven gated PET/CT: implications for lesion segmentation and quantitation

Abstract: Background Data-driven gating (DDG) can improve PET quantitation and alleviate many issues with patient motion. However, misregistration between DDG-PET and CT may occur due to the distinct temporal resolutions of PET and CT and can be mitigated by DDG-CT. Here, the effects of misregistration and respiratory motion on PET quantitation and lesion segmentation were assessed with a new DDG-PET/CT method. Methods A low-dose cine-CT was acquired in misr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Instead, it can increase or decrease SUV max . For instance, we found that both motion correction and improved AC (either average CT or DDG CT) increased SUV max above any amount expected from noise with 50% reduced counts 20 . Separating the combined effects of motion correction, noise from reduced counts, and improved AC with DDG CT is not straightforward and would be part of other separate work, which is currently taking place.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Instead, it can increase or decrease SUV max . For instance, we found that both motion correction and improved AC (either average CT or DDG CT) increased SUV max above any amount expected from noise with 50% reduced counts 20 . Separating the combined effects of motion correction, noise from reduced counts, and improved AC with DDG CT is not straightforward and would be part of other separate work, which is currently taking place.…”
Section: Discussionmentioning
confidence: 91%
“…There was an increase in DDG PET image noise because it only retains 50% of the data used in routine PET. However, the increases in maximum standard uptake value (SUV max ) for tumors that are observed in our DDG PET/CT method originate from both motion correction (DDG PET) and improved registration from DDG CT rather than from the use of 50% of PET data 20 …”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…While data-driven respiratory gating methods for both 90 Y PET and CT are yet to be robustly implemented in clinical practice, it may be appropriate to perform device-based gating of both the PET and the CT components of post-SIRT therapy PET-CT verification imaging. Accurate alignment of CT and PET images within the quiescent phase has been shown to be important for quantification using 18 F and 68 Ga PET-CT [ 28 ], and this is expected to apply equally to 90 Y imaging.…”
Section: Discussionmentioning
confidence: 99%